The Effect of Leadership Style on Employee Performance at CV. Production Coalition - Aminah Harahap; Mustapa Sarifah Aini Kembaren; Ahmad Rama Wijaya; Muhammad Husein Habibi; Hastuti Olivia (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of leadership style on employee performance at Cv. Production Coalition. In this study using primary data research methods. The sample in this study were employees of Cv. Coalesi Production, totaling 35 respondents. The data was tested using SPSS Statistics 25. The sample data in this study used a questionnaire. The research analysis method used simple linear reference analysis. Based on the results of the t test, for the variable Building Organization (X) t count 7.081> t table (1.69236) with a significance of 0.000 <0.05. This shows that H0 is rejected and H1 is accepted, which means that there is a significant influence of leadership style on employee performance in cv. production coalition..